PERKEMBANGAN PENDIDIKAN ISLAM PADA MASA AWAL HINGGA LAHIRNYA KERAJAAN ISLAM DI ACEH: LEMBAGA DAN TOKOHNYA - Masruraini Masruraini; Bahaking Rama; Muhammad Rusydi Rasyid (CV. ADIBA ASIHA AMIRA, 2023)
This study aims to provide a comprehensive explanation regarding the history of the development of Islamic education in the early days until the birth of the Islamic kingdom in Aceh, institutions and figures who played a role in the development of Islam in Aceh. Basically, the effectiveness of the development of education in Indonesia is of course inseparable from the central actor who has a role in the process of the development of Islamization. There are many theories that actually have different opinions in providing reviews regarding how the process of Islam entered Indonesia, who brought it, when did it enter and where did its spread begin. Several theories note that the object of the development of Islam in Indonesia first occurred among the people of Aceh. The success and progress of education during the Islamic empire in Aceh could not be separated from the influence of the ruling Sultan and the role of the scholars and poets, both from outside and from the local area. then in the form of manasah, frame, dayah which in subsequent developments developed according to the demands of the times and technology.